GUAM AND THE SCO: COMPARATIVE ANALYSIS - SYROEZHKIN, Konstantin (CENTRAL ASIA AND THE CAUCASUS, 2008)
Numerous organizations have been born and died on the post-Soviet expanse; the larger part of them left no trace and there-fore can be safely forgotten. Two organizations, however, deserve our special attention. I have in mind the Organization for Democracy and Eco-nomic Development—GUAM and the Shanghai Cooperation Organization, not so much because they are rivals of sorts, but because the way they were formed and developed, their response to events, and many other things are similar. Any attempt to compare two international organizations is a thankless task, however, I shall under-take it here. The SCO and GUAM are not mere rivals—each of them is supported by outside players with great geopolitical ambitions. GUAM is backed by the United States joined recently by the European Union; the SCO has China behind it, which has great designs for the post-Soviet expanse. This ac-counts for their specifics and their attitudes toward Russia, which claims the role of key player on the post-Soviet expanse. Proof of the above is easily found in the two structures’ history, which reveals not merely the reasons for their emergence, but also the interests of the outside players involved. The SCO’s status is clear enough: China is obviously interested in it and is working hard to channel it in the desirable direction. Sometimes it succeeds, sometimes it fails, because so far it is treading cautiously so as not to irritate Russia. In short, it has to bear in mind Russia’s interests and ambitions. The expert community, however, agrees that the SCO was set up on China’s initiative, which needed a lever of influence in Central Asia.1 The Agreement on Confidence-Building Measures in the Military Sphere in Border Areas signed in April 1996 in Shanghai and its component, the Agreement on Mutual Reduction of Armed Forces in the Border Area signed in Moscow in April 1997, laid the foundation of the Shanghai Five; in the late 1990s it was transformed into the “Shanghai Forum,” which in June 2001 became the Shanghai Cooperation Organization.